A mitochondria-targeted fluorescent probe for selective detection of mitochondrial labile Fe(ii). Issue 6 (4th June 2018) - Hirayama, Tasuku; Kadota, Satoki; Niwa, Masato; Nagasawa, Hideko
Abstract : Development of a turn-on and selective fluorescent probe for mitochondrial labile Fe(ii ). Abstract : Mitochondria are iron-rich organelles that are involved in the process of energy production through the electron-transporting system and heme synthesis. We developed a new mitochondria-targeted fluorescent probe, MtFluNox /Ac-MtFluNox, for Fe(ii ) based on N-oxide chemistry, which we recently established as a Fe(ii )-selective fluorogenic switch. The deacetylated formMtFluNox showed a turn-on response towards Fe(ii ) with high metal selectivity in cuvette experiments, and an imaging study using its cell-compatible analogueAc-MtFluNox demonstrated mitochondria-specific fluorescence enhancement in response to Fe(ii ) in living cells. Furthermore, the probe was able to detect endogenously accumulated Fe(ii ) induced as a result of the inhibition of heme synthesis.